2015
DOI: 10.11613/bm.2015.023
|View full text |Cite
|
Sign up to set email alerts
|

How well are pregnant women in Croatia informed about the oral glucose tolerance test?

Abstract: IntroductionPreanalytical errors still constitute the largest source of errors in laboratory work. Proper patient preparation and patient’s knowledge about a particular procedure affects its accuracy and reliability. We hypothesized that most of pregnant women are not well enough informed about the proper procedure for the OGTT. The aims of this study were to investigate: (i) how well pregnant women are informed about the OGTT; (ii) the most common way to inform pregnant women about OGTT and (iii) whether preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…However, 83% of the patients knew that they were being tested for diabetes. A study by Patricija et al (6) on knowledge of OGTT protocol in pregnant women showed that 42% of the participants demonstrated high and 38% adequate level of knowledge about the OGTT procedure. Majority of participants were informed about the procedure by gynaecologist (56%).Our study was showing lesser percentage of patients being completely informed by their physician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 83% of the patients knew that they were being tested for diabetes. A study by Patricija et al (6) on knowledge of OGTT protocol in pregnant women showed that 42% of the participants demonstrated high and 38% adequate level of knowledge about the OGTT procedure. Majority of participants were informed about the procedure by gynaecologist (56%).Our study was showing lesser percentage of patients being completely informed by their physician.…”
Section: Discussionmentioning
confidence: 99%
“…According to Randle`s hypothesis (4) . (5,6) . One of the reasons could be lack of effective communication to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous ways of informing the patients: instructions on the laboratory website, leaflets or other educational material. Evidence has shown that patients tend to seek information from their physicians, rather than from laboratory [22,23]. However, Bankovic Radovanovic and Kocijancic had shown that pregnant women who have received information from the laboratory staff were better informed about oral glucose tolerance test than those who obtained instructions from their gynaecologist [22].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that patients tend to seek information from their physicians, rather than from laboratory [22,23]. However, Bankovic Radovanovic and Kocijancic had shown that pregnant women who have received information from the laboratory staff were better informed about oral glucose tolerance test than those who obtained instructions from their gynaecologist [22]. Thus, it is the responsibility of laboratories to educate physicians, whereas national societies for laboratory medicine should be more engaged in delivering recommendations and acting as a link between laboratories and physicians.…”
Section: Discussionmentioning
confidence: 99%
“…14. (Radovanovic & Kocijancic, 2015) Oral glucose tolerance test Gynaecologist, laboratory staff, internet, nowhere…”
mentioning
confidence: 99%